Micropiling and its fundamentals / Syed Ahmad Najib Syed Mohd Naim - Syed Mohd Naim, Syed Ahmad Najib (Universiti Teknologi MARA, Perak, 2012)
In general, this report explains briefly about the fundamentals and operation of a certain piling system; the micropile. It is based on the experience, knowledge and observance of the writer for 5 months on the construction site. This report is divided further into several parts which include the introduction on the topic chosen, the history and background of the company the writer was placed upon, the methods and sequence of work done based on the topic of choice and also the conclusion and opinion of the writer about the topic given. The introduction briefly explains the concepts of piling and how it gives support to any building. It also contains the methods used to ensure the completion of the report and also the objectives of the whole report. The second chapter involves the history, background and organizational chart of the company where the writer was placed upon. The methods and sequence of work consist of step by step measures that were taken to complete the work of piling at the construction site. As a whole, micropiling is a piling concept and system used based on the soil of a construction site. For this construction site, the soil was harder than any normal soil so a micropile was used to give the foundation needed for the soil.